1999
DOI: 10.1002/(sici)1096-9071(199909)59:1<38::aid-jmv7>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

GB virus C/hepatitis G virus infection in KwaZulu Natal, South Africa

Abstract: Sera from 70 patients on maintenance haemodialysis, 98 patients with chronic liver disease, and 232 volunteer blood donors in the province of KwaZulu Natal, South Africa, were screened for GB virus/hepatitis G virus (GBV-C/HGV) RNA and anti-E2 by reverse transcription-polymerase chain reaction (RT-PCR) and by an enzyme-linked immunosorbent assay (ELISA), respectively. GBV-C/HGV RNA was detected in 17/70 (24.3%) haemodialysis patients, 12/98 (12.2%) patients with chronic liver disease, and 44/232 (18.9%) blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…1999a). Phylogenetic analysis of the E2 gene segment from certain KZN isolates is consistent with previous analysis of the 5′ NCR(Sathar et al . 1999a; Smith et al .…”
Section: Phylogenetic Analysis Of Gbv‐c/hgvsupporting
confidence: 88%
See 1 more Smart Citation
“…1999a). Phylogenetic analysis of the E2 gene segment from certain KZN isolates is consistent with previous analysis of the 5′ NCR(Sathar et al . 1999a; Smith et al .…”
Section: Phylogenetic Analysis Of Gbv‐c/hgvsupporting
confidence: 88%
“…2000). Recently, a new variant of GBV‐C/HGV whose sequences of the 5′ NCR were different from all other known GBV‐C/HGV sequences was identified in the province of KwaZulu Natal (KZN), South Africa (Sathar et al . 1999a).…”
Section: Phylogenetic Analysis Of Gbv‐c/hgvmentioning
confidence: 99%
“…The prevalence of HGV antibody in different sex was found 3.2% (5/156) in males and 3.1% (3/96) in females. 15 It has been reported that 60%-70% patients develop antibodies after infection. 16 As such, the detection of HGV RNA and anti-E2 is necessary to accurately define the controls was 1 to 5 %, in thalassaemic children 32.6%, asymptomatic carriers of anti-HCV 20.4%, IDUs 18.2%, aplastic anaemia patient 14.3%, CSWs 10% and in chronic liver disease 10% 10. Diagnosis of HGV infection is usually carried out by testing serum for the viral genome and /or antiviral antibody.…”
Section: Resultmentioning
confidence: 99%
“…Prevalence of antibody to HGV in hemodialysis patients in Japan was reported as 7.8% 22 -10.7% 23 and 25.7% from South Africa 15 . Low prevalence of hepatitis G virus antibody in hemodialysis patients may be due to following reasons i) immunocompetent individuals develop antibody at a much higher ratio than immunodepressed patients 17 , ii) HGV infection may be more likely to persist in hemodialysis patients and seroconversion to anti E2 may be less likely to occur 24 and iii) it was also been suggested that seropositivity for anti E2 may be short lasting after seroconversion among hemodialysis patients.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological investigations demonstrated that GBV-C/HGV RNA prevalence among blood donors ranges from 0.5-4% in the USA, Europe and Japan (Orito et al 1996, Gutierrez et al 1997, Nübling et al 1997, Blair et al 1998, Sauleda et al 1999) to 10-18.9% in some African countries (Casteling et al 1998, El-Zayadi et al 1999, Sathar et al 1999. In South America, it has also been reported at a varying range from 5.5% in Argentina (Oubiña et al 1999) to 14.6% in Bolivia (Konomi et al 1999).…”
Section: Discussionmentioning
confidence: 99%